2020
DOI: 10.1136/bmjspcare-2020-002558
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use at the end of life: a scoping review

Abstract: ObjectiveTo examine antibiotic use in patients approaching end of life, in terms of frequency of prescription, aim of treatment, beneficial and adverse effects and contribution to the development of antimicrobial resistance.DesignScoping reviewData sourcesAn information scientist searched Ovid MEDLINE, Ovid EMBASE, The Cochrane library, PubMed Clinical Queries, NHS Evidence, Epistemonikos, SIGN, NICE, Google Scholar from inception to February 2019 for any study design including, but not limited to, randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…14 Another retrospective study from a tertiary medical center during 2019-2021 reported that 96% of cancer patients received antibiotics, 76.5% received antibiotic combinations during EOL care, and 81.1% received antibiotics until death. 15 Regarding the factors of antibiotic use in patients nearing the EOL, literature reviews by Fairweather et al 16 and Macedo et al 17 reveal inconsistencies and challenges in antibiotic decision-making for EOL patients, driven by ethical and legal uncertainties. The unpredictability of death, even during EOL care, may raise concerns about the potential for reversing infectious diseases in terminally ill patients, and the complex nature of these patients' conditions often makes the diagnosis of infections difficult, if not impossible.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another retrospective study from a tertiary medical center during 2019-2021 reported that 96% of cancer patients received antibiotics, 76.5% received antibiotic combinations during EOL care, and 81.1% received antibiotics until death. 15 Regarding the factors of antibiotic use in patients nearing the EOL, literature reviews by Fairweather et al 16 and Macedo et al 17 reveal inconsistencies and challenges in antibiotic decision-making for EOL patients, driven by ethical and legal uncertainties. The unpredictability of death, even during EOL care, may raise concerns about the potential for reversing infectious diseases in terminally ill patients, and the complex nature of these patients' conditions often makes the diagnosis of infections difficult, if not impossible.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 scoping review suggests that antibiotics do provide a limited survival benefit to some patients nearing the end of life and may also mitigate symptoms associated with certain infections such as urinary tract infections; however, these benefits may come at the cost of prolonging the dying process, compounding adverse effects, and promoting antibiotic resistance. 22 Existing stewardship guidelines including AOF guidelinesdo not typically reflect the challenges surrounding prescription decisions at the end of life, ultimately limiting their use among terminally ill patients. Therefore, a focus for future stewardship efforts may be to develop guidance to help providers navigate discussions surrounding antibiotic use at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Multicomponent nursing home interventions that have been tested in randomized clinical trials (RCTs) and have been shown to reduce antimicrobial use have not been adopted into practice. Despite the need to align antimicrobial use at the end-of-life with goals of care, efforts to improve infection management in nursing homes have not integrated infectious disease and palliative care principles nor have they focused on residents with advanced dementia.…”
Section: Introductionmentioning
confidence: 99%